L1 Transfer in the Acquisition of Tense and Aspect Morphology: an Empirical Study of Chinese learners of Spanish as a Second Language - Quintana Hernández, Lucía; Bo, Zhang (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The aim of this paper is to show that the use of grammatical aspect in Spanish L2 is twofold biased by the Chinese L1 temporal representation and lexical aspect in intermediate level. The analysis of the use of Spanish past tenses by Chinese learners will take into account the L1 Transfer Hypothesis (Nishi y Shirai, 2019), the Lexical Aspect Hypothesis (Andersen y Shirai, 1994 y 1996), and the Lexical Underspecification Hypothesis (Giacalone-Ramat y Rastelli, 2008; Rastelli, 2009). To that end, three different tasks (multiple-choice, translation, controlled written production) were designed, and their results were analysed through chi-square and SPSS tests. The results show that Chinese learners use two patterns in the process of acquisition of Spanish past verbal morphology. On the one hand, they use the Spanish present perfect in perfective contexts; on the other hand, and against grammatical expectations in Spanish, they misuse punctual predicates (achievements) with duration adverbials, which verifies both the predictions of the L1 Transfer Hypothesis and the Lexical Underspecification Hypothesis. The results also show preference for achievements with preterit in the production task, which confirms both the effect of lexical aspect and task type in the use of grammatical aspect. These findings reveal that the acquisition of temporal and aspectual representation in L2 is a complex process in which multiple factors interact with each other.